Novice teachers’ appraisal of expert feedback in a teacher professional development programme in Chinese vocational education - Jin, Xinglin; Tigelaar, Dineke; van der Want, Anna; Admiraal, Wilfried (Teaching and teacher education, 2022)
This study is focused on exploring novice teachers' appraisal of expert feedback in a professional development programme for vocational schoolteachers. Twelve novice teachers in different school subjects were interviewed after the programme. An appraisal framework with 4 domains and 12 appraisal categories was built based on coding and analysing interview transcripts. The most frequently occurring appraisal categories and the differences between Chinese language teachers and vocational subject teachers were also analysed qualitatively. The findings revealed novice teachers’ concerns and expectations for expert feedback, as well as provided an appraisal framework for future studies on feedback in teacher professional development. •A framework was built to appraise expert feedback in a TPD programme.•The most frequently mentioned appraisal domains refer to teacher characteristics and educational context.•The most frequently mentioned appraisal categories are feedback benefit, teachers' expertise and students' characteristics.•Novice teachers hold a pragmatic attitude towards expert feedback.•Novice teachers in different school subjects appraise expert feedback differently.